2021
DOI: 10.1111/jth.15266
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase expression and activity are increased in platelets during clinical sepsis

Abstract: Background: Heparanase (HPSE) is the only known mammalian enzyme that can degrade heparan sulfate. Heparan sulfate proteoglycans are essential components of the glycocalyx, and maintain physiological barriers between the blood and endothelial cells. HPSE increases during sepsis, which contributes to injurious glyocalyx degradation, loss of endothelial barrier function, and mortality.Objectives: As platelets are one of the most abundant cellular sources of HPSE, we sought to determine whether HPSE expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 58 publications
4
19
0
Order By: Relevance
“…Disruption of the endothelial glycocalyx is now considered to play a central role in the transient endothelial hyper-permeability (15,36). HPSE is a critical component of the glycocalyx function and has been linked to various diseases characterized by inflammation and plasma leakage such as sepsis, proteinuric kidney diseases and viral diseases like COVID-19 (12,17,18,31,35,(37)(38)(39). In line with our current findings, several ex vivo and in vitro studies have previously explored the role of HPSE protein in dengue (15,16,35).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Disruption of the endothelial glycocalyx is now considered to play a central role in the transient endothelial hyper-permeability (15,36). HPSE is a critical component of the glycocalyx function and has been linked to various diseases characterized by inflammation and plasma leakage such as sepsis, proteinuric kidney diseases and viral diseases like COVID-19 (12,17,18,31,35,(37)(38)(39). In line with our current findings, several ex vivo and in vitro studies have previously explored the role of HPSE protein in dengue (15,16,35).…”
Section: Discussionsupporting
confidence: 80%
“…Remarkably, a recent study suggested the increase of HPSE mRNA expression as well as enzymatic activity in platelets of sepsis patients, which was associated with sepsis-associated mortality (35). Since platelet activation, as well as coagulation activation are prominent features of dengue, we further explored the possible role of platelets to the observed increased plasma HPSE activity and presence of endothelial glycocalyx degradation products in plasma from dengue patients.…”
Section: Increased Plasma Hpse Activitymentioning
confidence: 89%
“…More recently, both Hpa-1 expression and activity were found to be elevated in platelets during human sepsis. The active 50 kDa form of Hpa-1 in platelets, not its 65 kDa proenzyme though, correlated with mortality [81] . Whether increased Hpa-1 expression and activity in thrombocytes of septic patients is mechanistically associated with increased risk of thrombus formation, still needs to be explored.…”
Section: Heparan-sulfate and Its Cleavage Enzyme Heparanase-1mentioning
confidence: 84%
“…Nevertheless, it has an increased activity in most organs thus contributing to multi-organ failure (i.e. ARDS, AKI, intestinal barrier dysfunction) [38] , [39] , [79] , [80] , [81] , [82] , [83] .…”
Section: Heparan-sulfate and Its Cleavage Enzyme Heparanase-1mentioning
confidence: 99%
“…Increasing heparinase expression is associated with worse clinical outcome, possibly due to loss of the protective vascular glycocalyx leading to oedema and vascular injury. 131 Studies using the platelet releasate from healthy volunteers induced an anti-inflammatory phenotype in DCs similar to that elucidated by PMPs. Given the changes in the proteome and transcriptome in the context of sepsis, it would be interesting to examine whether this represents a context-dependent effect or is a general feature of the platelet releasate.…”
Section: Platelet-derived Evs and The Platelet Proteome/ Secretome In Sepsismentioning
confidence: 87%